2018
DOI: 10.1111/mmi.13974
|View full text |Cite
|
Sign up to set email alerts
|

The hetZ gene indirectly regulates heterocyst development at the level of pattern formation in Anabaena sp. strain PCC 7120

Abstract: Multicellular development requires the careful orchestration of gene expression to correctly create and position specialized cells. In the filamentous cyanobacterium Anabaena sp. strain PCC 7120, nitrogen-fixing heterocysts are differentiated from vegetative cells in a reproducibly periodic and physiologically relevant pattern. While many genetic factors required for heterocyst development have been identified, the role of HetZ has remained unclear. Here, we present evidence to clarify the requirement of hetZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 58 publications
1
29
1
Order By: Relevance
“…Videau et al showed that deletion of hetZ blocked the induced expression of hetR, hetP and patS [30]. A similar effect of hetZ mutation on the expression of patS had been shown in our previous study [27].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Videau et al showed that deletion of hetZ blocked the induced expression of hetR, hetP and patS [30]. A similar effect of hetZ mutation on the expression of patS had been shown in our previous study [27].…”
Section: Discussionsupporting
confidence: 84%
“…The expression of patS was shown to be dependent on hetZ rather than hetP (S1 Fig). Consistently, patS was upregulated in a Δ hetP mutant but not in a Δ hetZ mutant [30].…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…hetR encodes a master regulator of heterocyst differentiation, and its overexpression causes heterocyst formation in the presence of nitrogen sources (13). Both hetP and hetZ are directly upregulated by HetR, and ectopic expression of either gene leads to heterocyst formation in the presence of nitrogen sources (4,(36)(37)(38)(39)(40). hepA encodes a component of an ABC transporter required for the construction of the heterocyst exopolysaccharide layer (41), which is the first step during morphological differentiation (4).…”
Section: Resultsmentioning
confidence: 99%